Homodiselenacalix[4]arenes: Molecules with Unique Channelled Crystal Structures. Issue 3 (7th December 2015) - Thomas, Joice; Dobrzańska, Liliana; Van Meervelt, Luc; Quevedo, Mario Alfredo; Woźniak, Krzysztof; Stachowicz, Marcin; Smet, Mario; Maes, Wouter; Dehaen, Wim
Abstract: A synthetic route towards homodiselenacalix[4]arene macrocycles is presented, based on the dynamic covalent chemistry of diselenides. The calixarene inner rim is decorated with either alkoxy or tert ‐butyl ester groups. Single‐crystal X‐ray analysis of two THF solvates with methoxy and ethoxy substituents reveals the high similarity of their molecular structures and alterations on the supramolecular level. In both crystal structures, solvent channels are present and differ in both shape and capacity. Furthermore, the methoxy‐substituted macrocycle undergoes a single‐crystal‐to‐single‐crystal transformation during which the molecular structure changes its conformation from 1, 3‐alternate (loaded with THF/water) to 1, 2‐alternate (apohost form). Molecular modelling techniques were applied to explore the conformational and energetic behaviour of the macrocycles. Abstract : Change the channel : A new family of calixarene macrocycles, homodiselenacalix[4]arenes (see figure), was prepared by applying the dynamic covalent chemistry of diselenide bonds. In the single crystal, the calixarene molecules can switch between two conformations in a concerted fashion as a response to the right external stimuli.